Photocatalytic Oxidation of Acetone Over High Thermally Stable TiO2 Nanosheets With Exposed (001) Facets - Shi, Ting; Duan, Youyu; Lv, Kangle; Hu, Zhao; Li, Qin; Li, Mei; Li, Xiaofang (Frontiers in Chemistry, 2018)
Anatase TiO2 (A-TiO2) usually exhibits superior photocatalytic activity than rutile TiO2 (R-TiO2). However, the phase transformation from A-TiO2 to R-TiO2 will inevitably happens when the calcination temperature is up to 600 oC, which hampers the practical applications of TiO2 photocatalysis in hyperthermal situations. In this paper, high energy faceted TiO2 nanosheets (TiO2-NSs) with super thermal stability was prepared by calcination of TiOF2 cubes. With increase in the calcination temperature from 300 to 600 oC, TiOF2 transforms into TiO2 hollow nanoboxes (TiO2-HNBs) assembly from TiO2-NSs via Ostwald Rippening process. Almost all of the TiO2-HNBs are disassembled into discrete TiO2-NSs when calcination temperature is higher than 700 oC. Phase transformation from A-TiO2 to R-TiO2 begins at 1000 oC. Only when the calcination temperature is higher than 1200 oC can all the TiO2-NSs transforms into R-TiO2. The 500 oC-calcined sample (T500) exhibits the highest photoreactivity towards acetone oxidation possibly because of the production of high energy TiO2-NSs with exposed high energy (001) facets and the surface adsorbed fluorine. Surface oxygen vacancy, due to the heat-induced removal of surface adsorbed fluoride ions, is responsible for the high thermal stability of TiO2-NSs which are prepared by calcination of TiOF2 cubes.